A jump-training program that focuses on controlled landings, strengthening the hamstrings, and proprioception shows promise at preventing ACL tears - Metz, G. (Training & Conditioning, 1999)
From high school-level participation to the WNBA, women's basketball has never been more popular. We see more women flying to the hoop on our television screens than ever before, and athletic directors are putting more and more money into this potential revenue-producing program. Behind the scenes, however, many athletic trainers fear there is one thing holding the game back: way too many ACL injuries. As we've written about before in these pages (see Training & Conditioning, October 1996), research shows that the incidence of significant knee injuries among females is roughly five times higher per player hour than that for males. And the sport of basketball has been hit hardest. From Nikki McCray to Kellie Jolly, women hoopsters too often count scars along with baskets and rebounds. As research continues on why--theories include basic anatomical differences between the genders, hormonal influences, and/or neuromuscular deficiencies among females--Tim Hewett, PhD, the Director of Applied Research at the Cincinnati Sportsmedicine Research and Education Foundation, and his colleagues have been focusing on how--how to prevent knee injuries in female athletes. And they seem to have found some solutions. Over the past six years, Hewett and his group have developed a training program that has been tested on high school female basketball, volleyball, and soccer players, which significantly decreased their incidence of ACL ruptures. The program also improved athletes' vertical jumping ability. The results, which were presented at last year's annual meeting of the American Orthopedic Society for Sports Medicine, are in press in the American Journal of Sports Medicine. In the study, Hewett and his colleagues recruited 43 sports teams (girls' and boys' soccer and basketball, and girls' volleyball)--a total of 1,263 student-athletes--consisting of 366 girls who would go through the program and 463 girls who would not, along with 434 boys who would also not be trained and would serve as the control population. Ninety-four percent of the athletes were followed for at least four weeks--the minimum required for inclusion in the study. Athletic trainers at each school then tracked serious knee injury rates, defined as a knee ligament sprain or rupture that forced the athlete to lose at least five consecutive days of practice and competition. All ACL ruptures were confirmed by arthroscopy and MCL sprains were diagnosed based on pain along the MCL and increased rotation with a valgus stress test. No re-injuries were included in the study. At six weeks, there were 14 serious knee injuries: 10 of them among the untrained girls, two among the trained girls, and two among the untrained boys. Both injuries sustained among the trained girls resulted from direct physical contact with another player; eight of the 10 among the untrained girls were non-contact.